2022
DOI: 10.1108/apjml-12-2021-0934
|View full text |Cite
|
Sign up to set email alerts
|

Exploring consumer purchase intention in cross-border e-commerce: evidence from ‘belt and road’ countries

Abstract: PurposeThe purpose of this paper is to explore the determinants of consumer purchase intention (CPI) of cross-border e-commerce (CBEC) in the countries of the Belt and Road Initiative (BRI).Design/methodology/approachThis study proposes a research model of the antecedents of CPI on CBEC in BRI countries. Study participants were consumers with CBEC shopping experience in BRI-associated countries (n = 278). Structural equation modeling was used to test the research model.FindingsTrust has the greatest effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
0
6
0
2
Order By: Relevance
“…Comparatively, based on the data analysis of the returned products, customer behaviour can be examined (Truc Doan et al, 2018). Jian et al (2022) in their study highlighted that customers prefer not to be charged for the costs of returning the products. Customers believe that a favourable return policy means better product quality and a better shopping experience.…”
Section: Reverse Logistics Management In the Fast Fashion Industrymentioning
confidence: 99%
“…Comparatively, based on the data analysis of the returned products, customer behaviour can be examined (Truc Doan et al, 2018). Jian et al (2022) in their study highlighted that customers prefer not to be charged for the costs of returning the products. Customers believe that a favourable return policy means better product quality and a better shopping experience.…”
Section: Reverse Logistics Management In the Fast Fashion Industrymentioning
confidence: 99%
“…Several studies have revealed their research motivations under these supportive policies (e.g., Jian et al, 2022;Mou et al, 2019;. As Giuffrida et al (2017, p. 789) rightly argued, CBEC is enabling China to be not only an important exporting country (as used to be) but also an importing country with growing consumer demand (Figure 4).…”
Section: Research Regions and Cbec-related Policiesmentioning
confidence: 99%
“…From the perspective of China, the Belt and Road Initiative (B&R), which was adopted by the Chinese government in 2013 to delineate the global infrastructure development strategy, and the ‘Internet Plus’ strategy, which was proposed in 2015 and emphasized the integration and application of information technology, has propelled CBEC research in China. Several studies have revealed their research motivations under these supportive policies (e.g., Jian et al, 2022; Mou et al, 2019; Mou, Cui, & Kurcz, 2020). As Giuffrida et al (2017, p. 789) rightly argued, CBEC is enabling China to be not only an important exporting country (as used to be) but also an importing country with growing consumer demand (Figure 4).…”
Section: Descriptive Analysismentioning
confidence: 99%
See 2 more Smart Citations